Pesquisa de Brucella spp. em linfonodos de suínos e javalis com linfadenite - Vicente, Acácia Ferreira [UNESP] (2013)
Pork is the most consumed source of animal protein in worldwide. Brucellosis is one of the most important and worldwide distributed zoonosis. The prevention of human brucellosis depends on controlling the disease in animals. The bacteria isolation is the standard technique but new molecular methods allow the detection and differentiation the agent in species and biotypes reducing the time required for the final diagnosis. The control and eradication programs are based in serological tests for the diagnosis, however, variation in these tests according to different countries and researchers are common. In Brazil reports for seropositivity in swine range from zero to 100% depending on region, sampling and methodology, but studies of the disease in suidae with lymphadenitis are not found. This study aims to describe the epidemiological situation of brucellosis in pigs in Brazil and evaluate Brucella agar, CITA and Farrell culture media for isolation of the bacteria and to detect the presence of the agent in lymph nodes of pigs and boars with lymphadenitis slaughtered in the state of São Paulo and sent for human consumption